Makna Teologis Kepastian Keselamatan Dalam 1 Yohanes 5:11-13 - Sumampouw, Alexander; Gulo, Refamati (Vieka Wahana Semesta, 2024)
Abstract: The news of salvation in the Bible is one of the doctrines that is very important to be understood and understood well and believed by every person who believes. In fact, almost all religions teach about salvation, in fact all religions have claims about all the ways and rules on how someone can be saved. In Christianity itself the teaching about salvation is a very important and essential teaching. The Bible teaches how people can be saved through Jesus Christ, the purpose of being saved, how to convey the news of salvation to all other people which is the duty and calling of believers or the church. Even the most important thing is how believers have a firm belief that when someone makes the decision to believe in Jesus Christ as Lord and Savior, they have the certainty of eternal salvation.